Lexical and Grammatical Characteristics of the Belarusian Translation of Chapter 1 and 2 of The Gospel of Matthew (Catholic and Orthodox Editions, 2017) - Pankou, Yauhen (Poznańskie Studia Slawistyczne, 2023)
This article provides a comparative analysis of certain lexical and grammatical peculiarities in the Catholic and Orthodox editions of the Belarusian translation of Chapters 1 and 2 of the Gospel of Matthew in the New Testament. The study is based on biblical textual sources in Belarusian, Polish, Greek and Russian, including explanatory and other dictionaries, as well as works on modern Belarusian literary lexicology. It is emphasized that while adapting the Gospel of Matthew into Belarusian, translators exhibit a certain dependence on the influence of foreign languages and the traditions of confessional writing, thus sometimes disregarding encyclopedic variants, or ignoring lexical, semantic and grammatical processes characteristic of the modern Belarusian literary language.